Toll-like receptor-2 induced inflammation causes local bone formation and activates canonical Wnt signaling - Henning, Petra; Kassem, Ali; Westerlund, Anna; Lundberg, Pernilla; Engdahl, Cecilia; Lionikaite, Vikte; Wikström, Pernilla; Wu, Jianyao; Li, Lei; Lindholm, Catharina; de Souza, Pedro P. C.; Movérare-Skrtic, Sofia; et al. (Frontiers in Immunology, 2024)
It is well established that inflammatory processes in the vicinity of bone often induce osteoclast formation and bone resorption. Effects of inflammatory processes on bone formation are less studied. Therefore, we investigated the effect of locally induced inflammation on bone formation. Toll-like receptor (TLR) 2 agonists LPS from Porphyromonas gingivalis and PAM2 were injected once subcutaneously above mouse calvarial bones. After five days, both agonists induced bone formation mainly at endocranial surfaces. The injection resulted in progressively increased calvarial thickness during 21 days. Excessive new bone formation was mainly observed separated from bone resorption cavities. Anti-RANKL did not affect the increase of bone formation. Inflammation caused increased bone formation rate due to increased mineralizing surfaces as assessed by dynamic histomorphometry. In areas close to new bone formation, an abundance of proliferating cells was observed as well as cells robustly stained for Runx2 and alkaline phosphatase. PAM2 increased the mRNA expression of Lrp5, Lrp6 and Wnt7b, and decreased the expression of Sost and Dkk1. In situ hybridization demonstrated decreased Sost mRNA expression in osteocytes present in old bone. An abundance of cells expressed Wnt7b in Runx2-positive osteoblasts and ß-catenin in areas with new bone formation. These data demonstrate that inflammation, not only induces osteoclastogenesis, but also locally activates canonical WNT signaling and stimulates new bone formation independent on bone resorption.